2012
DOI: 10.1177/0018726711429382
|View full text |Cite
|
Sign up to set email alerts
|

Good morning, good day: A diary study on positive emotions, hope, and work engagement

Abstract: The objective of this diary study was to look at the potential positive within-person relationships between positive emotions, work-related hope, and the three dimensions of work engagement on a daily level (i.e. vigor, dedication, and absorption). Following Broaden-and-Build theory and Affective Events Theory, it was expected that the experience of positive emotions would cause hope, which in turn would lead to a state of vigor, dedication, and absorption. The study was conducted among 59 employees of a Dutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(229 citation statements)
references
References 80 publications
(140 reference statements)
14
203
0
12
Order By: Relevance
“…Furthermore, research has shown that positive emotions build hope on a daily basis (Ouweneel et al, 2012). In addition, people who experience positive emotions show increases in optimism (Fredrickson et al, 2003).…”
mentioning
confidence: 99%
“…Furthermore, research has shown that positive emotions build hope on a daily basis (Ouweneel et al, 2012). In addition, people who experience positive emotions show increases in optimism (Fredrickson et al, 2003).…”
mentioning
confidence: 99%
“…Work engagement and positive emotions are both forms of positive affect (Oerlemans & Bakker, 2013). Whereas work engagement (active positive affect) is enduring and stable, positive emotions are fluctuating and fleeting (Ouweneel, Le Blanc, Schaufeli, & van Wijhe, 2012). Some researchers found that positive affect encourages the use of intuition (Elsbach & Barr, 1999;Sinclair, 2011).…”
Section: Hypothesis 1amentioning
confidence: 99%
“…Based on a more refined acceptance probability estimate, one can also consider modeling the prospective author behaviour by weighting the effort she needs to put in preparing a submission against the probability of acceptance and potential benefits such as increased scientific visibility. Similarly to positive emotions affecting work engagement mediated by hope [69], we expect that positive emotions associated with a paper accepted at a prestigious conference in the preceding year give rise to hope, making the author to be more inclined to submit the paper in the year afterwards. Using these kinds of models, conference organisers can obtain additional insights in the impact of different policies recommended in the literature, such as increasing the acceptance rate, on future submissions (cf.…”
Section: Using the Datamentioning
confidence: 99%